2021
DOI: 10.1186/s12940-021-00746-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cardiovascular mortality, stroke and coronary heart mortality associated with aircraft noise around Congonhas airport, São Paulo, Brazil: a small-area study

Abstract: Background Noise pollution is increasingly recognised as a public health hazard, yet limited evidence is available from low- and middle-income countries (LMIC), particularly for specific sources. Here, we investigated the association between day-night average (Ldn) aircraft noise and the risk of death due to cardiovascular disease (CVD), stroke and coronary heart disease (CHD) at small-area level around São Paulo‘s Congonhas airport, Brazil during the period 2011–2016. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Yet, limited research has examined associations between aircraft noise exposure and CVD. 3,5,6,[18][19][20][21][22][23][24][25][26] Within the United States, only a few studies have been conducted, in which authors found relationships between aircraft noise exposure and CVD-related events, yet were limited to zip-code-level data 18 or one time point of exposure data. [24][25][26] Furthermore, previous literature has shown mixed results when examining relationships between aircraft noise and CVD incidence, CVD mortality, and all-cause mortality.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, limited research has examined associations between aircraft noise exposure and CVD. 3,5,6,[18][19][20][21][22][23][24][25][26] Within the United States, only a few studies have been conducted, in which authors found relationships between aircraft noise exposure and CVD-related events, yet were limited to zip-code-level data 18 or one time point of exposure data. [24][25][26] Furthermore, previous literature has shown mixed results when examining relationships between aircraft noise and CVD incidence, CVD mortality, and all-cause mortality.…”
Section: What This Study Addsmentioning
confidence: 99%
“…[24][25][26] Furthermore, previous literature has shown mixed results when examining relationships between aircraft noise and CVD incidence, CVD mortality, and all-cause mortality. 3,5,6,[18][19][20][21][22][23] In a longitudinal study examining modeled annual average exposures to aircraft noise in Switzerland, the authors found positive associations between noise and mortality from myocardial infarction (MI) comparing ≥60 dB(A) with <45 dB(A), but not with all-cause or other cardiovascular-specific mortality. 19 In an updated study from Vienneau et al on the same cohort with extended years from 2000 to 2011, investigators reported associations of noise with mortality from CVD and CVD-subtype mortality.…”
Section: What This Study Addsmentioning
confidence: 99%
“…The harmful health effects of aircraft noise have repeatedly been demonstrated in a large number of studies and include a wide range of different effects from annoyance due to noise [ 1 , 2 ], sleep disturbance [ 3 , 4 ], increased risks for cardiovascular diseases [ 5 , 6 , 7 ], myocardial infarction [ 8 ], hypertension [ 9 ] and coronary heart disease [ 6 ] as well as decreased mental health [ 10 ]. Annoyance and disturbance due to noise [ 1 ] can be considered as one of the most important effects of noise.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to aircraft noise has been associated with a variety of different adverse health outcomes [1]. These range from annoyance due to noise [2][3][4][5][6], sleep disturbance during the night [7][8][9][10][11], associations with cardiovascular diseases [12], myocardial infarction [13], coronary heart disease [14], and blood pressure [15]. The harmful effect of noise has already been demonstrated for infants and children, on health, perception, and learning, e.g., through the deterioration of reading and oral comprehension in school children [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%